Membranes for guided bone regeneration in dentistry: a review of human randomized blinded clinical trials - Marlus da Silva Pedrosa; Maria Natally Belchior Fontenele; Luiz Gustavo Fernandes Lima Oliveira; Wendersom da Silva do Amaral; Carmem Dolores Vilarinho Soares de Moura; Cláudio Heliomar Vicente da Silva; Lívia Duarte Santos Lopes (Associação Brasileira de Odontologia, 2018)
Objective: to review the literature currently available on membranes for guided bone regeneration in clinical dental practice. Material and Methods: a literature search was performed on PubMed, Web of Science and Scopus. The Jadad Scale was used for data collection and selection. The quality of the studies was evaluated through Cochrane Center Guidelines. Randomized and blinded clinical trials published in Portuguese, Spanish and English were included. Literature reviews of studies without randomization and blinding or when a percentage equal to or greater than 20% of the sample did not proceed with the study follow-up were excluded. We selected 27 studies that were categorized according to the findings. Results: the number of publications found limited the conclusions on the success of GBR in dentistry. Conclusion: the variety of techniques and membranes applied, as well as the small number of studies found are in need of well-designed studies in order to better evaluate the potential of GBR in patients submitted to these treatment approaches, as well as to determine accurate treatment protocols.